A Versatile Pre and Post Ugi Modification for the Synthesis of Natural Product Inspired Fused Peptide‐Carboline Scaffolds as Potential Anti‐Leishmanial Agents. Issue 42 (13th November 2019) - Khan, Irfan; Singh, Jaybir; Kumar, Vivek; Verma, Ved Prakash; Shukla, Monika; Dhasmana, Anupam; Naruka, Puspendera Singh; Goswami, Ajay Kumar; Ameta, Keshav Lalit; Khan, Shahnawaz
Abstract: A series of novel β ‐ carboline‐peptide (5 a‐5 f )/ tetrahydro‐β‐carbolines‐peptide (10 a‐10 f ) has been synthesized via natural product inspired molecular hybridization approach. All the hybrids were examined for their anti‐leishmanial potential. Most of the screened derivatives exhibited significant in vitro anti‐leishmanial activity against promastigote and intracellular amastigotes (IC50 ranging from 2.43 to 7.61   μ M) than the control, miltefosine (IC50 = 8.2  μ M), with less cytotoxicity in comparison to the standard drugs (sodium stibogluconate, and miltefosine). Compound 5 a was also able to inhibit Leishmania donovani TR (LdTR). A molecular modeling study based on docking and subsequent binding free energy evaluation was carry out in the active site of LdTR to understand their possible binding site. Our results show that prototype 1 (5 a‐5 f ) & 2 (10 a‐10 f ) represent a new structural lead for anti‐leishmanial Chemotherapy. Abstract : We have recognized two β‐carboline‐peptide/ tetrahydro‐β‐carbolines‐peptide hybrid prototypes as novel class of potent anti‐leishmanial agents. Compound 5 a and 5 f demonstrate promising activity against promastigote and amastigote. We were also established compound 5 a and 5 f as Trypanothione Reductase (TR) inhibitor via LdTR enzymatic activity. The LdTR enzymatic activity inhibition was also supported by docking study. NO generation experiment and construction of host protective cytokines in murine macrophages induced by compounds 5 a was enhanced the anti‐leishmanial activity.